As Computer Users Grow More Savvy: Experiences with a Multimedia Tool - Bargeron, David; Grudin, Jonathan (Hawaii International Conference on System Sciences, 2004)
Software that can be widely used with little or no modification has advantages for producers and consumers. But it is likely to require some adjustment by users. We describe more than three years of studies of a conceptually simple multimedia annotation tool, which we expected to be widely useful without modification. We encountered a surprising range of specific requirements, including context- and content-specific needs that forced us to shift from an application focus to a platform focus. Instead of a single general-purpose tool, we ended up producing a toolkit to support asynchronous group interaction, with which many task-specific applications were built. This has far-reaching implications. For application designers, software developers, and researchers. As computer users become more aware of the versatility and flexibility of software, general purpose shrinkwrap software may fade away.